Prevalence and correlates of facemask usage during the second wave of COVID-19 pandemic in Uganda. - Nelson Onira Alema; Christopher Okot; Emmanuel Olal; Eric Nzirakaindi Ikoona; Freddy Wathum Drinkwater Oyat; Steven Baguma; Denish Omoya Ochula; Patrick Odong Olwedo; Johnson Nyeko Oloya; Francis Pebalo Pebolo; Pamela Okot Atim; Godfrey Smart Okot; et al. (PLOS Global Public Health)
The World Health Organization (WHO) and the United States Centers for Disease Control and Prevention (US CDC) documented wearing facemasks in public as one of the most important prevention measures to limit COVID-19 spread. Considering this, WHO and the US CDC developed guidelines for wearing facemasks in public. This study aimed to determine the prevalence and correlates of facemask wearing during the COVID-19 pandemic in northern Uganda. We conducted a cross-sectional study on 587 adults across nine districts in northern Uganda, across 24 high-volume health facilities offering free COVID-9 vaccines. Respondents were selected from the health facilities using a single-stage systematic sampling method. Data was collected in a face-to-face questionnaire interview with an internal validity of Cronbach's α = 0.72 and entered into Excel. A local Institutional Research Board (IRB) approved the study, and Stata 18 was used for data analysis using Modified Poisson Regression to generate prevalence ratios (PR) and adjusted prevalence ratios (aPR), with a p-value set at < 0.05. The reported prevalence of facemask wearing in public among respondents was high [88.7%,95%CI:86%,-91%]. A multivariate analysis found that obese respondents and those who were receptive (agreed) to the lockdown measures were respectively,1.12 times more likely to wear facemasks [aPR = 1.12,95%CI:1.04-1.19;p < 0.01], and1.23 times more likely to wear facemasks [aPR = 1.23, 95%CI:1.07-1.41;p < 0.01]. The most significant finding from this study was the high prevalence of self-reported facemask wearing among adult community members in northern Uganda. The correlates of wearing facemasks were, being obese and agreeing with the presidential directives on the lockdown measures. Although this prevalence is within acceptable rates, the strict enforcement of the practice by security forces has raised concerns among many community members and human rights advocates. We recommend more studies on communities' perspectives on the challenges and benefits of facemask-wearing after the COVID-19 pandemic.